Explaining the influence of enterprise architecture planning on information technology performance : a resource based view of the firm - Huni, Thaku (My University, 2013)
The concept of Architecture has received widespread acceptance within the construction industry. However, its importance within the Information Technology industry is a contested one. Critics of Architecture in the Information Technology (IT) industry posit that there is inadequate evidence to assume that it makes a difference to performance of IT. Enterprises increasingly need to ensure that they leverage their IT benefits not only within their silos but across business units. This need has driven ideas to introduce enterprise-wide blueprints or Enterprise Architecture (EA) Planning solutions to guide them in the design and implementation of IT. This study uses a quantitative survey to attempt to answer two questions: 1) What factors influence EA Planning within organizations? 2) To what extent does EA Planning improve IT performance? The Diffusion of Innovation theory (Compatibility, Ease of Use and Relative Advantage) was used to investigate the use of EA Planning whilst the Resource Based View of the Firm was used to investigate the performance impact of EA Planning. IT Performance is measured by Heterogeneity of Physical IT Infrastructure, Replication of IT Infrastructure Services, Business Application Integration and Enterprise Data Integration. EA Planning is measured by EA Planning Human Capital, IT Infrastructure Flexibility and Partnership Quality. Data was collected from 90 architects, some from South African consulting companies and the rest from architects around the world linked to popular Enterprise Architecture virtual communities. The key findings were significant relationships between the following for the factors that influence use of EA Planning: Compatibility and IT Infrastructure Flexibility; Ease of Use of EA Planning Policies and EA Planning Human Capital; Relative Advantage and EA Planning Partnership Quality. Significant relationships were found between the following for factors that influence IT Performance: EA Planning Human Capital and IT Performance (a combination of Enterprise Data Integration, Business Application Integration, Replication of IT Infrastructure Service and Heterogeneity of Physical IT Infrastructure); EA Planning IT Infrastructure Flexibility and Heterogeneity of Physical IT Infrastructure; EA Planning IT Infrastructure Flexibility and Business Application Integration. EA Planning Partnership Quality was rejected as a determinant of IT Performance. This study sheds light on how resistance to EA Planning can be reduced and also highlights the potential benefits of EA Planning in organizations. The implications will directly affect the relationship between EA practitioners and IT projects.
Keywords: Enterprise architecture; IT performance